Doubting the Impartiality: Constitutional Court Judges and Conflict of Interest - Idul Rishan (Jurnal Jurisprudence, 2022)
The Constitutional Court ruling on the third amendment to the Law on the Constitutional Court is worth discussing. In the judicial review, the justices judged a case in which they have interests. The interests are related to a requirement for being a Constitutional Court justice, term of office for Constitutional Court justices, and term of office for the chief justice and deputy chief justice. Can they be impartial? This study is aimed at three things. First, analyzing their interpretation through legal annotation. Second, identifying impacts the ruling has on the Constitutional Court. Third, providing a road map for judicial review related to Constitutional Court judges. This is mixed legal research using primary and secondary data. This study has found that the judges are not impartial due to conflict of interest. They have compromised universal principles of the judiciary. For the sake of impartiality, they should not be judges in their own cause. Instead, the Supreme Court should have the authority to review legislation on them.